Police communications and social media - Fielding, Nigel G. (European journal of criminology, 2023)
This article considers the affordances of Web 2.0 social media tools for public communications by the police and illustrates their use, presenting data from exploratory fieldwork with officers and staff in five UK police forces. Future lines of development are noted that may merit ongoing research.